N01 A 6-years experience of genetic counselling in Huntington disease (2006–2011): constant socio-demographic profile of at-risk individuals requesting genetic predictive test. (29th August 2012) - Nanetti, L; Ferruta, A; Gellera, C; Castaldo, A; Panzeri, M; Di Bella, D; Nespolo, C; Astori, S; Mariotti, C
Abstract : Objective: To report a 6-year experience of a programme for predictive test (PT) in Huntington disease (HD). Participants and Methods: At-risk individuals for HD, aged >18 years, performed three consecutive visits, and an optional follow-up visit at 4–6 months. Symptom Check List 90 Revised (SCL90 R), and Beck Depression Inventory (BDI) tests were administered. The psychiatrist/psychologist did not meet the at-risk subjects during the PT, but cooperated with the multidisciplinary team integrating psychological support at the disclosure of genetic results. Results: From 2006 and 2011, 159 individuals (78M/81F) at-risk for HD underwent the programme for PT. The mean age was 37.4±11.6 years (range 16–77) Married subjects were 51.3%. Positive symptoms at the SCL90R test were 26.0± 17.6 (range 1–78). Age, sex, marital status and results at psychological tests were similar in each year of the study. Only years of education were significantly lower for the subjects asking for PT in 2011 (10 years) in comparison with the subjects performing PT in 2006 (13.3) (p=0.0065). None of the subjects had clinically relevant depressive symptoms (BDI scores <19). Thirty-four subjects (21.3%) did not complete the programme. Seventy-three per cent of cases presented only mild psychological distress not requiring psychological support; while in 27% of cases psychological support was recommended (86% were mutation carriers) (p=0.0001). No suicidal attempts, self-harming or psychotic episodes were associated with the disclosure of unfavourable genetic results. Conclusions: During the 6 years of the programme we did not observe significant adverse events. Socio-demographic characteristics of the at-risk HD population undergoing PT remained similar from 2006 to 2011, except for education.